The concept of «perezhivanie» in the works of L.S. Vygotsky and the prospects for its consideration in the modern theory and practice of special psychology - Sinitsa, T.I. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
Context and relevance. The concept of "perezhivanie" is not fully developed by L.S. Vygotsky, but it is quite often encountered in his latest works. In his works, L.S. Vygotsky seems to be groping for the content of the concept of "perezhivanie", and at the same time he writes about experience (perezhivanie) as a dynamic unit of consciousness. The development of defectology, and then special psychology, as a scientific psychological direction working with children with special needs, is inextricably linked with the name of Lev Semenovich Vygotsky. Actualization of the concept of "perezhivanie" can be of particular importance in the context of psychological and pedagogical assistance to special needs children, strengthening its humanistic focus, as well as operationally clarifying methodological developments. Objective. To determine the role of the concept of "perezhivanie" in the value system of special psychology, and how this concept changes the attitude to the theory and practice of working with children with special needs. Methods and materials. Theoretical analysis of the works of L.S. Vygotsky and his followers, as well as a phenomenological description of stories from the practice of interaction with a special child and his relatives, which demonstrate the value of experience that changes the attitude to reality and the behavior of children with special needs. Results. The analysis indicates the prospects for the concept of "perezhivanie" to change the paradigm of research within the framework of developing cultural-historical psychology in general and special psychology in particular. Conclusions. The development of the concept of "perezhivanie" can open a new dimension in the theory and practice of psychological and pedagogical work with special needs children, their families, as well as in the topic of inclusion - in organizing the process of including a special child in society. Контекст и актуальность. Понятие «переживание» у Л.С. Выготского не является в полной мере разработанным, но достаточно часто встречается в его последних работах. Л.С. Выготский в своих работах как бы нащупывает содержание понятия «переживание», и при этом именно о переживании пишет как о динамической единице сознания. Развитие дефектологии, а затем и специальной психологии как научного психологического направления, работающего с детьми с особенностями в развитии, неразрывно связано с именем Льва Семеновича Выготского. Актуализация понятия «переживание» может иметь важное значение в контексте психолого-педагогической помощи особенным детям, усиливая ее гуманистическую направленность, а также операционально уточняя методические разработки. Цель. Определить роль понятия «переживание» в системе ценностей специальной психологии, а также то, каким образом это понятие изменяет отношение к теории и практике работы с детьми с особенностями развития. Методы и материалы. Теоретический анализ работ Л.С. Выготского и его последователей, а также феноменологическое описание историй из практики взаимодействия с особенным ребенком и его близкими, в которых проявляется ценность переживания, изменяющего отношение к действительности и поведение детей с особенностями в развитии. Результаты. Проведенный анализ указывает на перспективность разработки понятия «переживание» для смены парадигмы исследований в рамках культурно-исторической психологии в целом и специальной психологии в частности. Выводы. Разработка понятия «переживание» может открыть новое измерение в теории и практике психолого-педагогической работы с особенными детьми, их семьями, а также в теме инклюзии - в организации процесса включения особенного ребенка в общество.